Pengaruh Citra Merek dan Promosi terhadap Loyalitas Wisatawan melalui Variabel Intervening Kepuasan Wisatawan Danau Shuji di Kabupaten Muara Enim - Pratama, Reggi Agustian; Rahayu, Sri; Yamalay, Fadhil (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to determine the effect of brand image and promotion on loyalty through the intervening variable of Shuji Lake Tourist Satisfaction in Muara Enim Regency. Sampling used the Hair formula, with the sample used was 225 respondents who visited the Shuji Lake tourist spot, Muara Enim Regency. The data needed is primary data obtained from the distribution of questionnaires to tourists at Shuji Lake tourist attractions. The analytical technique used in this study is a structural equation modeling (SEM) analysis technique. The results of the SEM analysis technique show that firstly, brand image has a significant positive effect on loyalty, secondly, promotion has no effect on loyalty, thirdly, brand image has a positive and significant effect on satisfaction, four promotions have a negative but significant effect on satisfaction, and fifth, satisfaction has a significant positive effect on loyalty. Sixth, with the intervening variable strengthening the influence of the brand image variable on loyalty, seventh with the satisfaction intervening variable, promotion has a negative but significant effect on loyalty.